DEVELOPMENT AND COMPARISON OF MATHEMATIC MOBILE LEARNING BY USING EXELEARNING 2.0 PROGRAM AND MIT INVENTOR 2 - Tri Nova Hasti Yunianta; Anissa Putri; Dani Kusuma (Jurnal Infinity, 2019)
Mathematics mobile learning influences student learning outcomes. Making this application need skills and also the appropriate programs. The first goal in this study is to develop valid and effective mathematics mobile learning. The second goal in this study if using two different programs it would get the same or different results, is it different between the two applications made with different programs? This type of research is research and development (R & D). The first application research subjects were mathematics teachers and 8th grade students of Junior High School in Salatiga consisted of 28 students and the subjects in this study were divided into two, namely students in the 8G class who used the mobile learning application and who did not use it and this study was conducted in the second semester academic year 2014/2015. The second application research subject was 10th-grade students of Senior High School in Salatiga, consisted of 24 students. This research was conducted in the second semester of the academic year 2015/2016. The first application development model was using ASSURE Model and developed with ExeLearning program, while the second application used the ADDIE Model and developed with MIT Inventor 2 program. Data on learning outcomes were obtained by giving initial tests and final tests. Data were analyzed using N-gain enhancement test. The mathematics mobile learning application used the ExeLearning 2.0 program to obtain validation results with very good criteria for the display and material sections while for the improvement of student learning outcomes in the high category amounting to 0.7. The second mathematics mobile learning application obtained very good display validation results and for the material section in the good category, while the increase in learning outcomes obtained an increase in the high category which was 0.71. Both of these applications possessed differences and the characteristics of mobile learning applications also depend on which software is used. It has a unique impression of using the ExeLearning 2.0 application and MIT Inventor 2.